Basal Cell Carcinoma Diagnosed by Dermoscopy in Dermatology Clinic of the Miguel Enríquez University Hospital - Delia María Gálvez Medina; Yurelbis Loida Lobaina Mejías; Juliette Massip Nicot; Lisbeth Fernández González; Carmen Oraida Tenorio Morión; Dayné Leyva Duthil (Revista Finlay)
Foundation: basal cell carcinoma is a very common malignant tumor in humans. It is considered locally invasive, also aggressive and destructive. Objective: to show the behavior of patients with basal cell carcinoma diagnosed by dermoscopy in dermatology clinic of the Miguel Enríquez University Hospital, between June 2020 and May 2021. Method: a descriptive, cross-sectional study was carried out to show the behavior of patients with basal cell carcinoma who attended the dermatology consultation at the Miguel Enríquez University Hospital from June 2020 to May 2021. The universe of study was made up of patients older than 18 years who presented one or more presumptive lesions of basal cell carcinoma less than 3 cm in diameter. The variables used were: age, sex, skin phototype, clinical forms, dermoscopic patterns, topography of the lesion, occupation related or not to sun exposure. We worked with absolute frequencies, percentage, mean, standard deviation, maximum and minimum values, the ratio, chi-square and student's t tests, with significance p≤0.05. Results: it prevailed in the elderly (66.4±14.9 years), in men (54.1 %), with phototype 2 (57.8 %), and in the nose 33.9 %. The nodular form was more frequent (41.3 %), occupation exposed to the sun (66.9 %), average size of the lesion 1.4 cm. Dermoscopy showed a predominance of arborizing vessels (73.4 %). By histology, 90.8 % of the cases were confirmed. Conclusions: the elderly prevailed among the patients, with phototype 2. The nodular form was more frequent, the average size of the lesion was 1.4 cm. Dermoscopy showed a predominance of arborizing vessels. Dermoscopy turned out to be a necessary tool for systematic use in dermatology.